Preliminary Anticonvulsant and Toxicity Screening of Substituted Benzylidenehydrazinyl-N-(6-substituted benzo[d]thiazol-2-yl)propanamides - Ruhi Ali; Nadeem Siddiqui (The Scientific World Journal)
Keeping in view the structural requirements suggested in the pharmacophore model for anticonvulsant activity, a new series of 3-(2-(substitutedbenzylidene)hydrazinyl)-N-(substituted benzo[d]thiazol-2-yl)-propanamides were synthesized with aromatic hydrophobic aryl ring (A), NH–C=O as hydrogen bonding domain (HBD), nitrogen atom as electron donor (D), and phenyl as distal aryl ring (C). Synthesized compounds were characterized by FTIR, 1H NMR, 13C NMR, mass spectroscopy, and elemental analysis. Preliminary in vivo anticonvulsant screening (phase I) was performed by two most adopted seizure models, maximal electroshock seizure (MES) and subcutaneous pentylenetetrazole (scPTZ). Based on anticonvulsant screening results, two compounds, 5h and 5p, were found to be most active; they exhibited activity comparable to standard drugs phenytoin (PHY) and carbamazepine (CBZ). These active compounds were subjected to phase II and phase III screening, where they displayed much higher protective index (PI) in comparison to the standard drugs. In phase IV screening, the bioavailability of active compounds was assessed on oral administration. Further, preliminary safety profiles of 5h and 5p were evaluated by the neurotoxicity testing and liver enzyme estimation.